Distribution and morphology of nitrergic neurons across functional domains of the rat primary somatosensory cortex - Nogueira-Campos, Anaelli A.; Finamore, Deborah M.; Imbiriba, Luis A.; Houzel, Jean C.; Franca, João G. (Frontiers in Neural Circuits, 2012)
The rat primary somatosensory cortex (S1) is remarkable for its conspicuous vertical compartmentalization in barrels and septal columns, which are additionally stratified in horizontal layers. Whereas excitatory neurons from each of these compartments perform different types of processing, the role of interneurons is much less clear. Among the numerous types of GABAergic interneurons, those producing nitric oxide (NO) are especially puzzling, since this gaseous messenger can modulate neural activity, synaptic plasticity and neurovascular coupling. We used a quantitative morphological approach to investigate whether nitrergic interneurons, which might therefore be considered both as NO volume diffusers and as elements of local circuitry, display features that could relate to barrel cortex architecture. In fixed brain sections, nitrergic interneurons can be revealed by histochemical processing for NADPH-diaphorase (NADPHd). Here, the dendritic arbors of nitrergic neurons from different compartments of area S1 were 3D reconstructed from serial 200-μm thick sections, using 100x objective and the Neurolucida system. Standard morphological parameters were extracted for all individual arbors and compared across columns and layers. Wedge analysis was used to compute dendritic orientation indices. Supragranular layers displayed the highest density of nitrergic neurons, whereas layer IV contained nitrergic neurons with largest soma area. The highest nitrergic neuronal density was found in septa, where dendrites were previously characterized as more extense and ramified than in barrels. Dendritic arbors were not confined to the boundaries of the column nor layer of their respective soma, being mostly double-tufted and vertically oriented, except in supragranular layers. These data strongly suggest that nitrergic interneurons adapt their morphology to the dynamics of processing performed by cortical compartments.